Guidelines for nurses and patients with chronic heart failure - S. A. Boytsov; F. T. Ageev; Z. N. Blankova; O. N. Svirida; Yu. L. Begrambekova (Кардиоваскулярная терапия и профилактика)
These guidelines were developed to improve the outpatient care service for patients with chronic heart failure by creating specialized offices in the structure of first-level medical organizations, whose staff includes specialized personnel of both senior and middle medical level.